Generative AI Integration in the Startup Ecosystem: A Technopreneurship Strategy to Increase Global Competitiveness - Ghina Fauziyyah; Mar’atus Solikhah (Worldwide Research Publishing, 2026)
The rapid development of Generative Artificial Intelligence (Generative AI) technology has driven significant transformations in the global startup ecosystem. This technology enables the automation of creative processes, faster data analysis, and more efficient digital product development. In the context of technopreneurship, the integration of generative AI is a strategic factor that can increase startups' innovation capacity while strengthening global competitiveness. However, understanding how the integration of generative AI technology can be optimized in technopreneurship strategies to improve startup competitiveness still requires more in-depth empirical studies. This study aims to analyze the influence of generative AI integration in the startup ecosystem on technopreneurship strategies and its impact on increasing startups' global competitiveness. This study uses a quantitative approach with an explanatory research method. Data were collected through a survey of founders and managers of technology-based startups that utilize digital innovation in their business activities. The sampling technique used purposive sampling with a total of 150 startups as respondents. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method to test the relationship between the research variables. The results of the study indicate that the integration of generative AI has a positive and significant impact on technopreneurship strategies and startups' global competitiveness. Furthermore, technopreneurship strategies are proven to act as a mediating factor, strengthening the relationship between the use of generative AI technology and increased startup competitiveness in the global market. These findings suggest that the use of generative AI, supported by innovative technological entrepreneurship strategies, can be a source of competitive advantage for startups in facing the dynamics of the global digital economy.